Pemanfaatan Chatgpt Sebagai Media Bantu Praktik Berpidato Metode Ekstemporan pada Siswa SMP PGRI 1 Palembang - Bella Lestari; Dessy Wardiah; Achmad Wahidy (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the use of ChatGPT as an aid in extemporaneous speech learning and its relationship to student engagement and speaking skills. This study used a qualitative approach with data collection techniques through observation, questionnaires, interviews, practical assessments, and documentation. The results showed that the use of ChatGPT supports a more structured learning process, especially in helping students find ideas, organize key points, and develop speech outlines. The use of ChatGPT is also associated with increased student engagement and positive responses during learning. In addition, there is a tendency for improvements in aspects of material mastery, speech structure, and student confidence, although speaking skills such as expression, gesture, and improvisation still vary and require continuous practice. Thus, ChatGPT plays a role as an aid that supports student readiness in practicing speaking, but the development of speaking skills still requires direct practice and teacher guidance.  Keywords: ChatGPT; Public Speaking Learning; Extemporaneous Method;Speaking Skills; Learning Media.